Exceptional conservation of horse–human gene order on X chromosome revealed by high-resolution radiation hybrid mapping - Raudsepp, Terje (National Academy of Sciences, 2004)
Development of a dense map of the horse genome is key to efforts aimed at identifying genes controlling health, reproduction, and performance. We herein report a high-resolution gene map of the horse (Equus caballus) X chromosome (ECAX) generated by developing and typing 116 gene-specific and 12 short tandem repeat markers on the 5,000-rad horse × hamster whole-genome radiation hybrid panel and mapping 29 gene loci by fluorescence in situ hybridization. The human X chromosome sequence was used as a template to select genes at 1-Mb intervals to develop equine orthologs. Coupled with our previous data, the new map comprises a total of 175 markers (139 genes and 36 short tandem repeats, of which 53 are fluorescence in situ hybridization mapped) distributed on average at ≈880-kb intervals along the chromosome. This is the densest and most uniformly distributed chromosomal map presently available in any mammalian species other than humans and rodents. Comparison of the horse and human X chromosome maps shows remarkable conservation of gene order along the entire span of the chromosomes, including the location of the centromere. An overview of the status of the horse map in relation to mouse, livestock, and companion animal species is also provided. The map will be instrumental for analysis of X linked health and fertility traits in horses by facilitating identification of targeted chromosomal regions for isolation of polymorphic markers, building bacterial artificial chromosome contigs, or sequencing.